High cell density and latent membrane protein 1 expression induce cleavage of the mixed lineage leukemia gene at 11q23 in nasopharyngeal carcinoma cell line - Yee, P.H.C; Sim, S.P (BioMed Central Ltd, 2010)
Peter Han-Chung Yee, Sai-Peng Sim